Guinness World Records, 2015. Gamer's edition - Glenday, Craig; Guinness World Records Limited ([London] : Guinness World Records Ltd., 2014)
Profiles video gaming systems and games from 2014, offering gaming records, a top-50 countdown of favorite games according to an online poll, interviews with game designers and industry experts, key developments in gaming hardware, gaming tips and trivia, and more.
Includes index.
Young Adult
Keywords: Video games -- Miscellanea; Video games -- Miscellanea; Video games; Computer games; Curiosities and wonders; World records